Terapi Sel Punca Mesenkimal Sumsum Tulang Tikus dalam Meregenerasi Sel Sitotrofoblas Nekrosis yang Dipapar Carbon Black (RAT BONE MARROW MESENCHYMAL STEM CELL THERAPY IN REGENERATING NECROTIC CYTOTROPHOBLAST CELL FOLLOWING EXPOSED TO CARBON BLACK) - ., Widjiati; Madyawati, Sri Pantja; ., Rimayanti; Achmad, Agung Budianto (Jurnal Veteriner, 2015)
The objective of this study is to find out the potency of Rat Bone Marrow Mesenchymal Stem Cell(RBMMSC) in regenerating necrotic cytotrophoblast cells of rats (Rattusnorvegicus) following exposure tocarbon black at day 6 of gestation at different time of exposure (6 days and 12 days). This study usedrandomized factorial design with two factors (gestation day and treatment). Forty-eight gravid femalerats were divided into six treatment groups i.e. (i) animals at day 6-11 gestation and not expose to carbonblack; (ii) 6-11 days gestation animals + 532mg/m3 carbon black for 4 hours; (iii) 6-11 days gestationanimals + 532mg/m3 carbon black for 4 hours +1x107/0.1ml RBMMSC intravenously; (iv) animals at day6-17 gestation and not expose to carbon black; (v) 6-17 days gestation animals + 532mg/m3 carbon blackfor 4 hours; (vi) 6-17 days gestation animals + 532mg/m3 carbon black for 4 hours +1x107/0.1ml RBMMSCintravenously, respectively. Data were analyzed using univariat analysis and analysis of variance. Theresults showed that there were no significance differences in regenerating necrotic cytotrophoblast betweenthe groups treated with RBMMSC and carbon black exposure. The results indicated that the stem celltherapy following exposure to carbon black was incapable in regenerating the necrotic cytotrophoblastcells.
Keywords: carbon black, stem cell therapy, rat bone marrow, cytotrophoblast